Biomechanical effect of an occlusal device for patients with an implant-supported fixed dental prosthesis under parafunctional loading: A 3D finite element analysis - Silva, Lorena S.; Verri, Fellippo R. [UNESP]; Lemos, Cleidiel A.A.; Martins, Christine M.; Pellizzer, Eduardo P. [UNESP]; de Souza Batista, Victor E. (Elsevier, 2021)
Statement of problem: Whether providing an occlusal device for a patient with bruxism and an implant-supported fixed dental prosthesis leads to improved biomechanics is unclear. Purpose: The purpose of this 3D finite element analysis (FEA) study was to evaluate the biomechanical behavior of 3-unit implant-supported prostheses under parafunctional forces with and without an occlusal device. Materials and methods: Eight 3D models consisting of a posterior (type IV) maxillary bone block with 3 external hexagon implants (Ø4.0×7.0 mm) and 3-unit implant-supported prostheses with different crown connections (splinted or unsplinted) and an occlusal device under functional and parafunctional loading were simulated. The abutment screws were evaluated by von Mises stress maps, and the bone tissue by maximum principal stress and microstrain maps by using a finite element software program. Results: An occlusal device improved the biomechanical behavior of the prostheses by reducing stress in the abutment screws and stress and strain in the bone tissue. However, the use of an occlusal device was not sufficiently effective to negate the biomechanical benefit of splinting. Conclusions: The use of splinted crowns in the posterior maxillary region with an occlusal device was the most effective method of reducing stress in the abutment screws and stress and strain in the bone tissue when parafunction was modeled.